2022
DOI: 10.1159/000524150
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Impact of Lower Uterine Segment Contractions on Second Trimester Cervical Assessment

Abstract: Introduction: Asymptomatic contractions in the lower uterine segment (LUS) may affect uterocervical angle and cervical length; however, this has never been investigated. Therefore, the aim of this study was to evaluate the effect of LUS contractions on uterocervical angle, cervical length and LUS thickness. Materials and Methods: This was a prospective, observational, single-cohort study conducted on 102 asymptomatic singleton pregnancies between 19.0 and 22.6 weeks of gestation. Uterocervical angle and cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The anatomical and physiological changes, such as LUS contraction, might account for cervical length score variations 8,27,28 . When assessing the overall impact of LUS contraction on cervical length, it was found that for every 1‐mm increase in LUS thickness, the cervical length increased by 0.909 mm when the isthmus was included in the cervical length measurement equation 29 ; however, we demonstrated that scoring was improved after certification even in cases with LUS contraction present.…”
Section: Discussionmentioning
confidence: 68%
“…The anatomical and physiological changes, such as LUS contraction, might account for cervical length score variations 8,27,28 . When assessing the overall impact of LUS contraction on cervical length, it was found that for every 1‐mm increase in LUS thickness, the cervical length increased by 0.909 mm when the isthmus was included in the cervical length measurement equation 29 ; however, we demonstrated that scoring was improved after certification even in cases with LUS contraction present.…”
Section: Discussionmentioning
confidence: 68%